The Students’ Productive Skills through TRB Test to Support SMCP Implementation - Palayukan, Novianty; Limbong, Sunarlia; Nurfadilah, Auliyanti Sahril; Hatiffah, Nurul; Hasyari, Mutmainnah (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This research aimed to investigate the assessment of students’ productive skills (speaking and writing skills) through the Training Record Book (TRB) test in support of the implementation of Standard Marine Communication Phrases (SMCP). This research applied descriptive qualitative research. It was calculated first based on the aspects score of cadets’ speaking and writing skills, then described them in words qualitatively. The assessment Rubric by Brown (2004) and the semi-structured interview were applied in gathering the data which was conducted by cadets from Politeknik Ilmu Pelayaran Makassar. The speaking aspects overwhelmed grammar, vocabulary, pronunciation, and fluency. Meanwhile, the writing aspects involved organization, content, coherence, diction, grammar, and mechanics. The score range of each aspect was 1 to 4 with the score 1 being the lowest and the score 4 being the highest with their description. Then, a semi-structured interview was used in the research to obtain more data. In applying this type, the researchers provided a recorder, notes, and definitely some questions to ask, but remained flexibility so that other information could arise. Semi-structured interviews guided the researchers to investigate the cadets’ view of what was typically lacking and strong aspects of cadets' speaking and writing performance through the TRB test. The result of the research revealed that grammar is the lacking aspect for the cadets in both speaking and writing, while vocabulary and pronunciation were relatively stronger in speaking skills and the organization aspect was much stronger in writing skills. The research identified some reasons for this weaknesses including maladaptive language habits among seafarers, resistance to grammar learning, lack of motivation, student reluctance, and non-compliant speakers in speaking skills and students’ reluctance and Grammar resistance in the writing skills. This research revealed the crucial of concerning these weaknesses to improve the cadets’ ability to be able to communicate effectively so that it can lead to safety and operational efficiency.